Pengaruh Limbah Padat Pabrik Kertas Rokok Terhadap Beberapa Sifat Kimia Tanah Ultisol Tambunan A - Vika, Melina; Lubis, Kemala Sari; Damanik, M. M. B. (Universitas Sumatera Utara, 2017)
Solid waste of cigarette paper factory does not contain hazard and toxic materials but contain CaCO3 as a lime material. The research of was conducted to study effect of application of solid waste from the cigarette paper factory to improve soil properties at Ultisol Tambunan A. This research was conducted at the Laboratory of Soil Physics, Agriculture Faculty and analytic laboratory of socfindo company from May until June 2016. The research used non factorial completely randomized design consist (CRD) of four (4) treatment solid waste (cigarette paper factory) and five (5) replications, there are: L0 (control), L1 (0,4 g), L2 (0,6 g), and L3 (0.8 g). The results showed that the application of solid waste from cigarette paper significantly increase soil pH, P-available, Ca-exchangeble but not significantly increase K-exchangeable and organic carbon of Ultisol. Application of solid waste from cigarette paper significantly decrease Al-exchangeable and no significantly decrease Al-saturated of Ultisol.